Cabergoline toxicity: A case report (Indian Journal of Case Reports, 2024)
We are presenting a case of cabergoline toxicity in a patient with primary infertility; the main cause being high levels of prolactin (PRL). The aim was to examine this hyperprolactinemic patient, the ability to normalize the PRL levels with cabergoline, to determine the effectiveness, to assess the effect on clinical symptoms, and to determine its management. We prospectively studied this single hyperprolactinemic patient who was treated with cabergoline to normalize the PRL levels, but negative impacts were identified by cabergoline, patient was hospitalized, symptoms were documented, dermatologists, endocrinologists, and intensivists were also consulted for the same. As a result, the patient finally had a positive response and showed no signs of toxicity.